Anaplastic ganglioglioma with epithelioid cell components. Issue 5 (4th June 2018) - Murakami, Chiaki; Yamazaki, Tatsuya; Shintoku, Ryosuke; Aihara, Masanori; Yoshimoto, Yuhei; Matsumura, Nozomi; Nobusawa, Sumihito; Ikota, Hayato; Hirato, Junko; Yokoo, Hideaki
Abstract : A 40‐year‐old man was admitted to our hospital because of disorientation and mild left‐sided weakness. Radiological examination revealed a solid and cystic tumor in the right temporal lobe, and total resection was performed. Histologically, the tumor was composed mainly of low‐grade gangiloglioma and had some high‐grade glial components with focal necrosis and microvascular proliferations. In the high‐grade component, there were epithelioid cells with round cytoplasm and eccentric nuclei. The high‐grade area with epithelioid cells was intermingled within the low‐grade area, which suggests that epithelioid cells were an anaplastic transformation of ganglioglioma. The epithelioid cells were histologically similar to neoplastic cells of epithelioid glioblastoma (E‐GBM), a rare aggressive variant of isocitric dehydrogenase wild‐type glioblastoma. A BRAF V600E mutation, frequently observed in E‐GBM, was detected in both the ganglioglioma and epithelioid cell components. The epithelioid cells were mitotically active, which suggests that if the surgery was delayed, the histological appearance might have eventually evolved into E‐GBM. Indeed, a case of pleomorphic xanthoastrocytoma which transformed into E‐GBM after a long latency was reported elsewhere. This is the first report to describe focal epithelioid cells in anaplastic ganglioglioma.